Financial Distress Prediction with Grover Model: Case Study of PT Surya Pangan Indonesia - Mira, Mira; Rayyani, Wa Ode; Wahyudi, Fiqi (Invoice : Jurnal Ilmu Akuntansi, 2024)
This research aims to predict financial distress at PT Surya Pangan Indonesia using the Grover model and analyze the results using the Springate model. The study employs quantitative data sourced from the financial reports of PT Surya Pangan Indonesia for the years 2018, 2019, and 2020. The data analysis technique involves calculating financial ratios and applying the Grover and Springate models to determine the company's financial health. According to the Springate model, a score above 1.062 indicates a healthy financial condition, while a score below 0.862 suggests a serious threat of bankruptcy. The results reveal that in 2018 and 2019, PT Surya Pangan Indonesia was in a healthy financial state with Springate scores of 3.748 and 1.174, respectively. However, in 2020, the score dropped to 0.564, indicating severe financial distress. The decline is attributed to decreased profitability and sales amid the pandemic and fluctuating corn prices. This study underscores the importance of early financial distress detection using predictive models, enabling companies to implement corrective measures before reaching a crisis. The findings suggest that PT Surya Pangan Indonesia must enhance its financial management strategies to prevent future distress. Additionally, future researchers are encouraged to compare different financial distress prediction models, such as the Ohlson and Altman models, to develop a more comprehensive understanding of financial health in the Indonesian business context.